Policy Issues and Challenges in the Introduction of Electronic Toll Collection in Indonesia: A Qualitative System Dynamics Approach - Kamiliah, Dewi Ratih; Wijaya , Chandra (Migration Letters, 2023)
Objective: This study aims to analyze the policy issues and challenges involved in the implementation of Electronic Toll Collection (ETC) systems in Indonesia using a Qualitative System Dynamics (QSD) approach. Theoretical Framework: The research utilizes the System Dynamics framework, focusing on the qualitative phase, which involves constructing Causal Loop Diagrams (CLDs) to visually represent relationships and feedback loops in the ETC system. Method: The research applies a comprehensive literature review to identify key variables, causal relationships, and feedback loops relevant to ETC in Indonesia, followed by constructing CLDs based on the literature and validating these through expert consultations and stakeholder feedback. Results and Conclusion: The study develops a CLD tailored to the Indonesian context, identifying key policy issues and challenges in ETC implementation. These challenges are categorized into technology adoption, public acceptance, regulatory frameworks, and financing. The research underscores the need for a coordinated, holistic approach in addressing the various policy issues simultaneously to ensure successful ETC implementation in Indonesia. It highlights the importance of stakeholder collaboration, public acceptance, adequate financing, and robust regulatory frameworks. The findings provide valuable insights for policymakers, transportation agencies, and other stakeholders in Indonesia and contribute to the broader literature on transportation policy analysis.